Specialization in general practice - Hart, Julian Tudor (1980)
Ideas about general practitioner specialism may have been hampered in the past because of the three models of general practitioner specialism — in the hospital service, the fee-earning specialoid or the general practitioner obstetrician — none of which is satisfactory. However, general practitioner specialism can be justified in guaranteeing standards by concentrating groups of patients, accepting responsibility, and planning care. Medico-political changes may be needed to achieve improvement in clinical standards.